2014
DOI: 10.1007/s10164-014-0406-4
|View full text |Cite
|
Sign up to set email alerts
|

Prey size affects the costs and benefits of group predation in nymphs of the predatory stink bug Andrallus spinidens (Heteroptera: Pentatomidae)

Abstract: Group predation promotes foraging efficiency because it increases the size of prey that can be killed and improves hunting success compared to solitary predation. However, group predation may increase competition among group members during feeding. Earlier studies have focused on the advantages of group predation, but little is known about the costs and benefits of group predation for individual members of the group. Here, we show that the costs and benefits of group predation for individuals of the predatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…They reported a longer hunting time toward 6th instar larvae than 3rd and 4th instars. Also, the individual predatory bugs had longer hunting times than four predator groups and that the latter had a higher predation success against third and 4th instar larvae (Hyodo et al 2014). Taken collectively, the authors concluded that group predation has an advantage towards large prey mainly for early nymphs because of their smaller size and narrow host range which has been similarly observed in field observations (Manley 1982).…”
Section: Biologysupporting
confidence: 56%
See 1 more Smart Citation
“…They reported a longer hunting time toward 6th instar larvae than 3rd and 4th instars. Also, the individual predatory bugs had longer hunting times than four predator groups and that the latter had a higher predation success against third and 4th instar larvae (Hyodo et al 2014). Taken collectively, the authors concluded that group predation has an advantage towards large prey mainly for early nymphs because of their smaller size and narrow host range which has been similarly observed in field observations (Manley 1982).…”
Section: Biologysupporting
confidence: 56%
“…Such a response demonstrates that the predatory bug kills more individuals at a higher density of prey, with a constant search rate and saturation of predator (Shanker et al 2017). Hyodo et al (2014) designed a study to find the costs and benefits of group predation in A. spinidens. The authors believed in some advantages of group predation including the promotion of foraging efficiency, size of the prey and hunting success.…”
Section: Biologymentioning
confidence: 99%
“…Predaceous cimicomorphans and pentatomomorphans use their venoms primarily for immobilising, killing, and liquefying invertebrate prey. A key effect of venoms is rapid paralysis, which has been reported after envenomation by members of the Reduviidae [ 6 , 9 , 35 , 140 ], asopine Pentatomidae [ 141 ], predaceous Miridae [ 85 ], and predaceous Lygaeidae [ 142 ], and which may be much more widespread. The insecticidal activities of two reduviine assassin bug venoms have been quantified as LD 50 values of (dry weight of venom) 2 mg/kg ( H. innesi venom injected into larvae of the fly Sarcophaga argyrostoma ) [ 9 ] or 10.25 mg/kg ( P. rhadamanthus venom injected into the cockroach P. americana ) [ 6 ].…”
Section: Diversification Of Venom Pharmacology In the Evolution Ofmentioning
confidence: 99%
“…Among vertebrates, coordinated hunting is presently known with certainty in hominid primates (Boesch & Boesch, 1989;Stiner, Barkai, & Gopher, 2009), a few carnivores (Bailey et al, 2012;Creel & Creel, 1995;Eaton, 2009;Mech, 2007;Stander, 1992), cetaceans (Gazda, Connor, Edgar, & Cox, 2005;Smith, Siniff, Reichle, & Stone, 1981), two species of raptors (Bednarz, 1988;Leonardi, 1999), two species of corvids (Bowman, 2003;Yosef & Yosef, 2010), a few species of fish (Bshary, Hohner, Ait-El-Djoudi, & Fricke, 2006;Herbert-Read et al, 2016;Lönnstedt, Ferrari, & Chivers, 2014), crocodilians (Dinets, 2015), and monitor lizards (James & Fox, 2007;Pitman, 1931). As for invertebrates, coordination has never been demonstrated in any of the taxa known to hunt in groups (see Hyodo, Himuro, & Fujisaki, 2014), although coordination in post-hunt transportation of prey is known in ants (Lioni, Sauwens, Theraulaz, & Deneubourg, 2001).…”
mentioning
confidence: 99%